2023
DOI: 10.3389/fneur.2023.1209487
|View full text |Cite
|
Sign up to set email alerts
|

Cenobamate significantly improves seizure control in intellectually disabled patients with drug-resistant epilepsy and allows drug load reduction

Anna-Lena Friedo,
Benedikt Greshake,
Konstantin L. Makridis
et al.

Abstract: IntroductionEpilepsy patients with intellectual disability often suffer from drug-resistant epilepsy (DRE), which severely affects patients’ quality of life. Cenobamate (CNB) is a recently approved novel and effective ASM that can achieve high rates of seizure freedom in previously drug-resistant patients.MethodsWe performed a retrospective data analysis of the first patients treated with CNB at a single center. Outcome and treatment response were assessed at two different time points, and ASM burden was calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…In this retrospective, real-world study of CNB treatment in patients with drug resistant focal epilepsies, add-on CNB provided a clinically significant reduction in seizure frequency in most of the patients. The results we found in the current study are consistent with those observed in previously published randomized controlled trials (RCTs) (Chung et al, 2020;Krauss et al, 2020) and real-life experiences (Elliott et al, 2022;Makridis et al, 2022;Varughese et al, 2022;Beltrán-Corbellini et al, 2023;Friedo et al, 2023;Peña-Ceballos et al, 2023;Villanueva et al, 2023).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this retrospective, real-world study of CNB treatment in patients with drug resistant focal epilepsies, add-on CNB provided a clinically significant reduction in seizure frequency in most of the patients. The results we found in the current study are consistent with those observed in previously published randomized controlled trials (RCTs) (Chung et al, 2020;Krauss et al, 2020) and real-life experiences (Elliott et al, 2022;Makridis et al, 2022;Varughese et al, 2022;Beltrán-Corbellini et al, 2023;Friedo et al, 2023;Peña-Ceballos et al, 2023;Villanueva et al, 2023).…”
Section: Discussionsupporting
confidence: 92%
“…Finally, a drug load reduction was possible in 12 patients with developmental and epileptic encephalopathies, thanks to CNB effectiveness, maintaining seizures reduction (Friedo et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation